Democracy in transition economies: Grease or sand in the wheels of growth? - Jan Fidrmuc (EIB Papers, 2001)
After the communist regimes collapsed throughout Eastern Europe and the former Soviet Union, they were replaced (at least initially) by relatively wide-ranging democracy. Measured by the indices of political freedom and civil liberties published by the Freedom House (see the Technical Annex for more details), by 1993-two to three years after political liberalisation began-the Czech Republic, Hungary and Slovenia attained the same extent of democracy as the United Kingdom or Germany. Although other countries did not democratise as rapidly as the three front-runners, they still made considerable progress. Between 1989 and 1991, the average of the two Freedom House indices rose from 0.26 to 0.57, on a scale from zero (no democracy) to one (full democracy).
Keywords: 330; Demokratie; Deregulierung; Übergangswirtschaft; Wirtschaftswachstum; Schätzung; Osteuropa